2021
DOI: 10.21203/rs.3.rs-638041/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Micro Ring Resonator based CO2 Gas Sensor using PbSe Quantum Dots

Abstract: In this paper, we introduce a micro-ring resonator-based highly sensitive carbon dioxide sensor. For this purpose, a valley is created in the core of the ring and PbSe quantum dots (QDs) are deposited in the valley and the sensor is exposed to CO2 gas. In this way, the refractive index of the PbSe QDs increases with an increase in the concentration of gas flow, and then the resonance frequency of the ring resonator shifts. The designed sensor operates almost linearly over a wide range of concentrations for CO2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Therefore, CO 2 is also an important indicator of food quality and safety. Hajikhanloo et al (2021) developed a CO 2 sensor using micro-ring resonators, where they formed a valley in the center of the ring and deposited PbSe QDs in it. The study found that the refractive index of PbSe QDs exhibited a positive correlation with increasing CO 2 concentration, indicating that the sensor was effective in detecting CO 2 over a wide concentration range and had a detection limit of 0.001%.…”
Section: Volatile Componentsmentioning
confidence: 99%
“…Therefore, CO 2 is also an important indicator of food quality and safety. Hajikhanloo et al (2021) developed a CO 2 sensor using micro-ring resonators, where they formed a valley in the center of the ring and deposited PbSe QDs in it. The study found that the refractive index of PbSe QDs exhibited a positive correlation with increasing CO 2 concentration, indicating that the sensor was effective in detecting CO 2 over a wide concentration range and had a detection limit of 0.001%.…”
Section: Volatile Componentsmentioning
confidence: 99%